The influence of statistical aggregation measures and intervals for processing automated rut depth measurements on Pavement Management Systems - Steyn, Wynand JvdM (University of Pretoria, 2022)
Dissertation (MEng (Transportation Engineering))--University of Pretoria, 2021.